Microstructure, mechanical and corrosion properties of Mg–2Dy–xZn (x=0, 0.1, 0.5 and 1 at.%) alloys - Guangli Bi; Yuandong Li; Shijun Zang; Jianbin Zhang; Ying Ma; Yuan Hao (Journal of Magnesium and Alloys, 2014)
Microstructure, mechanical and corrosion properties of as-cast Mg–2Dy-xZn (x = 0, 0.1, 0.5, and 1) (at.%) alloys were investigated. The microstructures of the as-cast Mg–2Dy and Mg–2Dy–0.1Zn alloys mainly consisted of α-Mg phase and Mg24Dy5 eutectic phase. With 0.5 at.% Zn addition, Mg12ZnDy phase with 18R-type long period stacking ordered (LPSO) structure and Mg2Dy phase precipitated at the grain boundaries. When the content of Zn is 1 at.%, only the Mg3Zn3Dy2 phase formed in the α-Mg matrix. The electrochemical measurements and immersion testing results indicated that the Mg–2Dy–0.1Zn alloy exhibited the best corrosion resistance. It revealed that the morphology, scale, amount and distribution of the second phase have a great effect on the corrosion resistance of alloy. Additionally, the tensile testing results showed that the Mg–2Dy–0.5Zn alloy exhibited the higher tensile strength and good elongation, especially at 200 °C. The improvement of mechanical properties was mainly due to the strengthening of LPSO phase and grain refinement of α-Mg.